DESIGNING ARABIC LANGUAGE LESSON MATERIALS TO ENHANCE SPEAKING SKILLS AT AL-KAUTSAR INSTITUTE, TANJUNG PINANG - Aidillah Suja; Ramandha Rudwi Hantoro; Irsal Amin; Misbahul Munir (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The teaching material is an important element in the implementation of the learning process, as it serves as a source of information and a learning medium. Therefore, teachers should present teaching material that can achieve the learning objectives. Teaching material is one of the components in education that needs to be designed as best as possible, as it helps in designing the direction and goals of the learning process. Thus, designing teaching material is the most crucial aspect of the education and learning process. The teaching of Arabic in several schools, especially at the secondary level, is ineffective and inefficient. This is due to the diverse educational backgrounds of students and their lack of knowledge about the Arabic language. Therefore, there is a need for teaching material that can address these issues. One of the steps to tackle these problems is to innovate in education, and one of the ways is to develop teaching material that caters to the needs of students and the learning objectives. Hence, the aim of this research is to develop Arabic language teaching material to enhance students' speaking skills. The research method employed in this study is Design-Based Research (DBR). The results of this research include the development of Arabic language teaching material through three steps: 1) establishing learning objectives, 2) determining the lesson content, and 3) forming assessments. The validation of the developed Arabic language teaching material by experts, teachers, and students is good.